Protective effects of carvedilol on systemic vascular damage induced by angiotensin II: Organ-specific effects independent of antihypertensive effects - Vailati, Maria Do Carmo Fernandez [UNESP]; Rocha, Noeme Souza [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Padovani, Carlos Roberto [UNESP]; Schwartz, Denise Saretta; Matsubara, Beatriz Bojikian [UNESP] (My University, 2010)
Background: The protective effect of carvedilol on multiple organ damage induced by angiotensin II (Ang II) remains unclear. The aim of this study was to evaluate the protective effect of carvedilol on the heart, liver, and kidney in rats infused with Ang II. Material/Methods: Wistar rats were randomly distributed into three groups: control (no treatment), continuously infused with Ang II (150 ηg/min for 72 hr), and treated with Ang II + carvedilol (90 mg/kg/d). Histological sections of the myocardium, kidney, and liver were analyzed for the presence of necrosis. Results: Ang II induced arterial hypertension which was not affected by carvedilol treatment (tail-cuff blood pressures, control: 125±13.6, Ang II: 163±27.3, Ang II + CV: 178±39.8 mmHg, p<0.05). Also, there were perivascular inflammation and necrosis in the myocardium, kidney, and hepatocytes necrosis around the terminal vein. Carvedilol treatment fully prevented damage to the heart and kidney and attenuated liver lesions induced by the Ang II infusion. Conclusions: The protective effect of carvedilol on perivascular damage induced by Ang II infusion depended on the target organ. The prevention of heart damage occurred independently of the antihypertensive effects of carvedilol. © Med Sci Monit, 2010.
Keywords: Arteries; Beta-blockers; Hypertension; Necrosis